The Effect of Economic Growth, Unemployment Rate and Human Development Index on Poverty Rate in North Jakarta - Ni Made Nadia Resmarani; Sishadiyati (Jurnal Ekonomi dan Bisnis Digital, 2023)
Poverty is a complex problem, many factors affect the poverty rate in North Jakarta. This study aims to analyze the effect of economic growth, open unemployment rate, and human development index on the poverty rate in North Jakarta.iod 2009 to 2021, data was obtained through the Central Statistics Agency using multiple linear analysis methods using SPSS 27. The results of this study show that simultaneously Economic Growth, Unemployment Rate, and Human Development Index affect the Poverty Rate. Partial Economic Growth has no effect on the Poverty Rate, the Unemployment Rate has a positive impact in the Poverty Rate and the Human Development Index has a positive impact on the Poverty Rate.